Implementation of Two-Wheel Patrols by Samapta Malang City Polresta in Preventing the Crime of Theft (Advances in Police Science Research Journal, 2024)
This research is motivated by the importance of preventing motor vehicle theft as a top priority in maintaining order and security in the community of Malang City. The serious economic, psychological, and social impacts on motor vehicle theft victims are the main reasons why addressing this issue is essential. Although the police have formed the Turjawali Unit of the Samapta Unit to strengthen prevention efforts, challenges such as the success of perpetrators in seizing vehicles undetected and changes in crime patterns indicate the need for evaluation and enhancement of strategies. Technology, active community involvement, and a deep understanding of environmental factors are also key to strengthening prevention activities. Thus, preventing motor vehicle theft is not only about reducing crime rates but also about creating a safe and stable environment for the people of Malang City. Accordingly, this research aims to describe the management of two-wheeled patrol activities of the Malang City Samapta Police Unit in preventing motor vehicle theft and describe the resources supporting the two-wheeled patrol activities of the Malang City Samapta Police Unit in preventing motor vehicle theft. The theories and concepts used include the concept of motor vehicle theft, the concept of the Turjawali unit of the Samapta unit, the concept of two-wheeled patrol activities, management theory, and resource theory. The method used in this research is qualitative with a field research approach. The research results show that the management of two-wheeled patrols of the Malang City Samapta Police Unit is important in preventing motor vehicle theft. Although playing a vital role, challenges such as the lack of members and negative community responses still exist. They utilize various resources, but there is still a gap between the number of members and equipment. Lack of information about vulnerable areas is also a problem. Integrating physical, human, and organizational resources is key to enhancing prevention efforts.
Keywords: Kata Kunci: Pencegahan, tindak pidana pencurian kendaraan bermotor, patroli roda dua.